Amyloid-β Structure, Function, and Pathophysiological Significance in Neurodegenerative Diseases - Tanaka, Masashi; Ono, Kenjiro; Saito, Satoshi (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint includes 16 original articles published in a Special Issue that focuses on the pathological significance of amyloid-β in neurodegenerative diseases, such as Alzheimer's disease, the main cause of dementia. Collections in this reprint provide novel insights into the underlying mechanisms and therapeutic potentials of repositioning drugs and new agents for Alzheimer's disease and related dementias. These findings are expected to contribute to the development of innovative strategies for the prevention and treatment of such diseases.